Implementasi Model Problem Based Learning Berbantuan Media Counting Frog dalam Peningkatan Kecerdasan Logis Matematis - Dewi Lokasari; Panca Dewi Purwati; Watminingsih (Jurnal Pendidikan Indonesia (JOUPI), 2024)
Numeracy is one component of mathematical logical abilities. However, many elementary school students find difficulty in calculating. The objectives of this research are: (1) to describe the implementation of the Problem Based Learning model assisted by Canva-based Counting Fog media in improving mathematical logical abilities; 2) to describe the effectiveness of implementing the Problem Based Learning model assisted by Canva-based Counting Frog media in improving mathematical logical abilities. The population in this study was grade 1 students at SD Negeri 04 Ketringan, totaling nine students. The research design used is descriptive qualitative. The data collection techniques are observation, documentation and tests. The implementation of the Problem Based Learning model assisted by Canva-based Counting Frog Media is carried out using five PBL syntax. Media Counting Frog is used in the first syntax. The test results showed that there was an increase in the average pretest score from only 72.2 to 92.2 at posttest. So, it can be concluded that the implementation of the Problem Based Learning Model Assisted by Canva-Based Counting Frog Media can Improve Mathematical Logical Ability.